Determination of trace metals and analysis of arsenic species in tropical marine fishes from Spratly islands. Issue 1 (15th September 2017) - Li, Jingxi; Sun, Chengjun; Zheng, Li; Jiang, Fenghua; Wang, Shuai; Zhuang, Zhixia; Wang, Xiaoru
Abstract: Trace metal contents in 38 species of tropical marine fishes harvested from the Spratly islands of China were determined by microwave digestion and inductively coupled plasma mass spectrometry analysis. Arsenic species were determined by high-performance liquid chromatography and inductively coupled plasma mass spectrometry analysis. The average levels of Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo, Cd, Pb, and U in the fish samples were 1.683, 0.350, 0.367, 2.954, 36.615, 0.087, 0.319, 1.566, 21.946, 20.845, 2.526, 3.583, 0.225, 0.140, and 0.061 mg·kg − 1, respectively; Fe, Zn, and As were found at high concentrations. The trace metals exhibited significant positive correlation between each other, with r value of 0.610–0.852. Further analysis indicated that AsB (8.560–31.020 mg·kg − 1 ) was the dominant arsenic species in the fish samples and accounted for 31.48% to 47.24% of the total arsenic. As(III) and As(V) were detected at low concentrations, indicating minimal arsenic toxicity. Highlights: We determined the concentrations of trace metal in 38 species of tropical marine fishes from the Spratly islands. The differences of distribution and levels of arsenic species were explored in more species of tropical marine fishes. We evaluated the correlation and distribution characteristic of 15 trace metals in fish. The contamination degree of fish in the Spratly island sea area was assessed.